Case report of surgical management of a locally invasive colostomy adenocarcinoma. (2020) - Pearson, Lindsay; Chopyk, Daniel M.; Rosen, Seth A.
Highlights: Cancer at the site of a colostomy is quite rare. Management of the complex anatomic issues requires multi-disciplinary planning. Colon cancer screening should be performed in patients with colostomies. Abstract: Introduction: This case report involves the presentation and management of a locally invasive adenocarcinoma at the site of a colostomy in a patient with multiple comorbidities and anatomic constraints. Presentation of case: 63 year-old woman with a complicated medical and surgical history, including imperforate anus and permanent colostomy, who presented with a fungating mass at the site of her colostomy. Evaluation revealed a locally invasive adenocarcinoma requiring surgical management for symptom control and oncologic treatment. Discussion: Due to the patient's medical comorbidities, body habitus, prior surgery, prior radiation and locally invasive cancer, there were numerous physiologic and anatomic issues that required a multi-disciplinary approach. Specifically, consideration of the patient's prior radiation to the left chest, history of cystectomy and ileal conduit, history of prior colon resection, as well as her short stature and severe kyphosis required input from urology, plastic surgery and colorectal surgery for operative planning. The patient's chronic renal insufficiency, recurrent urinary tract infections and history of thromboembolic disease further complicated her perioperative management. Oncologic resection with wide local excision at the skin and abdominal wall were performed with mass closure of the midline and peristomal abdominoplasty, using mesh underlay. The patient's postoperative course was complicated by gastric outlet obstruction and recurrent urosepsis. Conclusions: Patients with chronic colostomies require colon cancer screening similar to their non-stoma peers, in accordance with national guidelines. Oncologic resection of cancers involving colostomies is feasible, but may require multi-disciplinary planning to manage complicated anatomic concerns.